Adaptation and stability analysis of sweet potato varieties for low-input systems in Uganda - Abidin, P.E.; Van Eeuwijk, F.A.; Stam, P.; Struik, P.C.; Malosetti, M.; Mwanga, R.O.M.; Odongo, B.; Hermann, M.; Carey, E.E. (Wiley, 2005)
Sixteen sweet potato varieties were evaluated for fresh storage root yield in 20 trials during 2000–2001 for three seasons in four locations in Uganda. Of the 16 varieties, 11 were developed by farmers and five by a central breeding programme. The behaviour of the varieties was quantified in terms of wide adaptation (genotypic mean across trials), specific adaptation (genotypic predictions for specific locations) and stability (Shukla stability variance). With respect to all three aspects of yield behaviour, farmer varieties performed on average better than the official varieties. The results illustrate the potential that farmer varieties can have in the improvement of sweet potato in Uganda and other regions where high diversity of sweet potato landraces exists.